2022
DOI: 10.3389/fpls.2022.1078377
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of cytochrome P450 multigene family and its differential expression analysis in pepper (Capsicum annuum L.)

Abstract: Plant cytochrome P450 is a multifamily enzyme widely involved in biochemical reactions for the synthesis of antioxidants, pigments, structural polymers, and defense-related compounds. Pepper (Capsicum annuum L.) is an economically important plant. A comprehensive identification and characterization of P450 genes would provide valuable information on the evolutionary relationships of genes and their functional characteristics. In this study, we identified P450 genes in pepper with the aid of bioinformatics meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(75 reference statements)
1
3
0
Order By: Relevance
“…The monogenic family CYP97 clan consists of two genes, namely IbCYP97A1 and IbCYP97B1. This is similar to the case of pepper (3 genes) [42]. These two genes are specifically expressed in the leaves and stems of sweet potato, indicating a potential relationship with the growth and development of sweet potato stems and leaves.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The monogenic family CYP97 clan consists of two genes, namely IbCYP97A1 and IbCYP97B1. This is similar to the case of pepper (3 genes) [42]. These two genes are specifically expressed in the leaves and stems of sweet potato, indicating a potential relationship with the growth and development of sweet potato stems and leaves.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, more members of the CYP450 gene family have been identified in other crops. For example, 326 CYP450 family members were identified in rice, 332 CYP450 genes in soybean, and 478 CYP450 genes in pepper [7,42,43]. This could be attributed to the fact that sweet potato's two genomes are too similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed that ABC transporters and MFS transporters enhance fungal resistance to toxic substances, including 2,4‐DAPG, closely related to MAPG 58–60 . The P450 family is present in almost all organisms, and extensively involved in the biosynthesis of antioxidants and defense molecules, playing a crucial role in combating harmful biotic stresses 61 . Therefore, cytochrome P450s, MFS transporter, and ABC transporter likely play important roles in the defense against MAPG toxicity in A. bisporus and may serve as candidate genes for disease resistance breeding.…”
Section: Discussionmentioning
confidence: 99%